COMPARISON BETWEEN MANUAL AND AUTOMATIC DELIMITATION OF CORUPÁ STREAM WATERSHED, RS, BRASIL - Goergen, Laura Camila de Godoy; Schuh, Mateus Sabadi; Pereira, Rudiney Soares (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611707277 Several environmental impacts such as deforestation, soil erosion, water pollution and chaoticurban occupation are related to lack of planning in land use in watersheds. For proper planningand management of water resources is critical to proper delineation of watersheds. Thus, thisstudy aimed to analyze a methodology for automatic delineation of watersheds in the basin of thecreek Corupá, Rio Grande do Sul/RS, Brazil, using design data Shuttle Radar Topographic Mission(SRTM) and compare with the values obtained in the area of manual scanning with based ontopographic maps with scale of 1:50 000. For this, the data were integrated and processed usingthe software ArcGIS 9.2 (ESRI, 2006). The methodology used in this process was divided into six stages, as follows: filling depressions ("fill sinks"), flow direction ("flow direction"), accumulatedflow ("flow accumulation"), extraction of drainage ("conditional - > con "), linking crossing stream("stream link ") and delineation of watersheds ("watershed"). The basin area delimited from thecontours of the topographical was 29.162,4 ha and for the automatic delineation met total area of28.472,2 ha, representing a difference of 2,4% of total area 690,2 ha. The results show very closevalues confirming be advantageous to automate the delineation of watersheds by several factorssuch as gratuity, the SRTM data accuracy and the great coverage of available data, since not allregions are data availability and the cartographic results may vary according to the humanperception.